(untitled) (World Bulletin of Management and Law, 2026)
This article examines drug addiction as a factor posing a serious threat to human development, social stability, and the national gene pool. The negative impact of narcotic substances on the human body - particularly on the brain, cardiovascular system, and mental health -is scientifically analyzed. Furthermore, the state policy of the Republic of Uzbekistan in combating drug abuse and drug-related crime is reviewed, including the content of the national strategy for 2024-2028 and presidential decrees. Based on statistical data, the relevance and urgency of this issue are substantiated. In conclusion, the importance of youth education, the formation of spiritual immunity, and the responsibility of all segments of society are emphasized.